2016
DOI: 10.1007/s00276-016-1662-5
|View full text |Cite
|
Sign up to set email alerts
|

Round window chamber and fustis: endoscopic anatomy and surgical implications

Abstract: The round window region is of critical importance in the anatomy of the middle ear. The aim of this paper is to describe its anatomy from an endoscopic point of view, emphasizing structures that have important surgical implications, in particular the fustis and the subcochlear canaliculus. The fustis, a smooth bony structure that forms the floor of the round window region, is a constant and important structure. It seems to indicate the round window membrane and the correct position of scala tympani. A structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…Recent studies underlined the importance of preoperative high resolution computed tomography (CT) findings and reported that the radiological evaluations correlated with the visibility of the RW [ 24 , 25 ]. Although the anatomical variations of the posterior tympanum and RW region were described in detail [ 26 ], problems in surgical orientation such as mistaking a wide subcochlear canaliculus with the RW niche may lead to inadvertent implantation attempts resulting in failure and other major complications may arise.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies underlined the importance of preoperative high resolution computed tomography (CT) findings and reported that the radiological evaluations correlated with the visibility of the RW [ 24 , 25 ]. Although the anatomical variations of the posterior tympanum and RW region were described in detail [ 26 ], problems in surgical orientation such as mistaking a wide subcochlear canaliculus with the RW niche may lead to inadvertent implantation attempts resulting in failure and other major complications may arise.…”
Section: Introductionmentioning
confidence: 99%
“…In literature, several authors have already studied the anatomy of this region. In particular, present authors have already described from an endoscopic perspective the ST, the pyramidal eminence with the subpyramidal space, the sinus subtimpanicus, and the round window niche with the subcochlear canaliculus . In 1969, Proctor had already described the microscopic surgical anatomy of the posterior tympanic wall and defined a system of sinuses around several permanent projections of the styloid complex, such as the pyramidal eminence, the styloid eminence, and the chordal eminence .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, present authors have already described from an endoscopic perspective the ST, 2,3 the pyramidal eminence with the subpyramidal space, 4 the sinus subtimpanicus, and the round window niche 9 with the subcochlear canaliculus. 5 In 1969, Proctor had already described the microscopic surgical anatomy of the posterior tympanic wall and defined a system of sinuses around several permanent projections of the styloid complex, such as the pyramidal eminence, the styloid eminence, and the chordal eminence. 10 The sinuses of the retrotympanum were the ST and PTS (positioned medial to the facial nerve), and the LTS and FS (positioned lateral to the facial nerve).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations